Tabular‐expression‐based method for constructing metamorphic relations. (23rd March 2020) - Li, Jingyao; Liu, Lei; Zhang, Peng
Summary: Metamorphic testing (MT) is proposed to overcome the oracle problem in software testing, and metamorphic relations (MRs) are the core of MT. There is a lack of guidelines for constructing effective MRs, and it is difficult to reuse MRs mainly because most MRs are closely related to the domain knowledge. In this article, we propose a method for constructing MRs from specifications in tabular expression format. Our method constructs MRs according to the characteristics of tabular expressions, especially the relationships between the header grids and the main grid, namely, our method is domain‐independent and the construction process is simplified. In addition, the derived MRs can be applied to specifications with the same tabular expression structure. For specifications with different tabular expression structures, MRs can still be used after slight adjustments. To evaluate the performance of our method in practice, we apply the method to five applications. The experimental results demonstrate that our method is effective for a program with the oracle problem, and that it is applicable to tabular expressions in various formats. Compared with representative testing methods, our method identifies errors that are not detected by the compared methods. Hence, our method and existing methods can complement each other. The MR proposed in this article outperforms MRs constructed based on program properties.